Innovation and Investment Strategies to Strengthen The Defence Industry and The Research and Development Capabilities of The Indonesian Army Through Triple Helix Collaboration - Hiras M. S. Turnip; Indra Kristian (The International Journal of Law Review and State Administration, 2026)
This study evaluates the effectiveness of the Indonesian Army's defence research and development (Litbanghan) ecosystem through a qualitative approach based on policy document analysis and quantitative prototype data. Analysis of 427 Litbanghan prototypes from 2006 to 2024 shows that only 3.9% entered mass production, indicating structural barriers in the downstream phase and weak integration between Litbang and Bangtekindhan. A review of regulations found gaps between the policy framework, such as Permenhan 16/2019 and Permenhan 39/2016, and implementation in the field, particularly in the certification process, incentive mechanisms, and clarity of intellectual property rights. An international comparative study (Turkey, Brazil, Portugal, South Korea) confirms that institutional coordination, sustainable research funding, and research-procurement connectivity are prerequisites for an effective defence innovation ecosystem. This study recommends increasing R&D funding, simplifying certification, establishing proportional IPR regulations, and integrating R&D results into the defence equipment procurement pipeline. Theoretically, this study expands the application of the Triple Helix model in the defence sector, which is characterised by strict regulations and a non-market environment. Practically, these findings provide strategic input for the formulation of the 2025–2029 Defence Industry Master Plan and the strengthening of national defence innovation governance.